Pengetahuan Agama Hindu Berwawasan Fenomena Sains - Darmayanti, Nyoman Sri (Metta : Jurnal Ilmu Multidisiplin, 2024)
Religion is necessary to help humans understand concrete experiences in living their lives in the world. Confidence in the truth of Hinduism needs to be strengthened amid today’s global life. To strengthen belief in Hindu religious values, there are a variety of studies of science phenomena that can reveal the truth of Hinduism, the aims this research to bring together scientific truths and normative truths of religion through phenomena in everyday life. This research uses a qualitative approach. The data source used is primary data sourced from literature. Data collection techniques were carried out using library and documentation methods. Data analysis of phenomena that occur among Hindus is studied scientifically through Hindu texts and science texts. The results of the search reference source suggest that intellectuals can prove the elements of science and technology contained in Hindu rituals. Hinduism has scientific methods for acquiring and developing science. The scientific method is called Catur Pramana, which is observation (pratyaksa), reasoning (anumana), modeling (upamana), and testimony (sabda). The conclusion obtained from study is if Hindus are convinced of God, they can understand Him by analogy and reflect on Hindu cosmology that learns about the ins and outs of the universe. Understanding of Brahman and Atman truths can be done through theistic or scientific paths through correct procedures.